Paleoambiente e icnofósseis da Formação Pimenteiras, devoniano da Bacia do Parnaíba, regiões de Valença do Piauí e Pimenteiras, Piauí - CUNHA, Lucas Noronha (Universidade Federal do Pará, 2019)
Shales and sandstones of the Pimenteiras Formation represent the most expressive records of Devonian seas in the Western Gondwana, exposed in the eastern border of Parnaíba Basin, Northern Brazil. This formation has been interpreted as storm-influenced platform deposits related to the transgressive phase during Mesodevonian to Neodevonian periods. Based-outcrop facies and stratigraphic analysis of the Pimenteiras Formation in the Valença do Piauí and Pimenteiras regions, State of Piauí, corroborated the previous interpretation of this unit, as well as allowed the identification of its ichnofossiliferous diversitity and abundance for the determination of paleoenvironmental parameters, such as sedimentation rate, oxygenation and bathymetry. Two facies associations were individualized for Pimenteiras Formation: 1) offshore/shoreface, characterized by hummocky cross-stratified sandstone interbedded with ripple bedded sandstone, massive sandstone and shale, configurating a pinch-and-swell pattern; and 2) upper offshore deposits, consisting by meterscale thick beds, laterally continuous by dozens of meter of shale, interbedded with hummocky cross-stratified sandstone. Systematic ichnology of Pimenteiras Formation indicated 15 ichnogenera, such as Agrichnium, Bergaueria, Bifungites, Circulichnis, Cruziana, Diplichnites, Helminthopsis, Lockeia, Lophoctenium, Palaeophycus, Phycosiphon, Planolites, Protopaleodictyon, Rusophycus and Zoophycos. The Agrichnium and Circulichnis ichnogenera are described for the first time in the Pimenteiras Formation. Different bioturbation levels occur restricted to sandstone beds were identified, with ichnofabric index (ii) 3, ranging between 15% and 25%. These average values of ii suggest typical oxygenation levels related to aerobic environments, or the sediment-water interface zone with reasonable oxygenation levels. These bioturbation levels are usually limited by shales with low (ii = 2) or none (ii = 1) bioturbation, suggesting an anaerobic environment near to the substrate. The Pimenteiras Formation includes the following ichnofacies representatives of offshore/shoreface transition: Skolithos, related to wave-dominated high energy environment; and Cruziana ichnofacies correspondent to the littoral zone and shallow to deep marine environment. The predominace of specimens of Cruziana with subordinate specimens of Skolithos ichnofacies in the studied deposits suggests a relationship with a permanent occupation of the substrate punctuated by episodic exploration of colonizers individues, after the storm events. The facies analysis in combination with ichnologic studies carried out in the Pimenteiras Formation provided important parameters for the understanding of sedimentary ix dynamic and substrate occupation by bentonic organism during the establishment of Devonian epicontinental seas in the Western Gondwana.